Identifikasi Boraks pada Jajanan Bakso Tusuk di Lombok Timur - Gemantari, Baiq Maylinda; Fatmayanti, Baiq Risma; Ramadhan, Leny (Jurnal Farmasi & Sains Indonesia, 2024)
Meatballs are a processed meat-based food commonly processed by adding chemical preservatives. Many reports find the usage of borax as the chemical preservative in meatballs sold in large markets on Lombok Island. However, the use of borax in the type of meatball consumed as snacks called skewered meatballs has not been identified thoroughly in East Lombok. This study aimed to identify borax in skewered meatballs in East Lombok qualitatively by curcumin paper test and flame test colors using sodium tetraborate as standard. The result showed that 4 samples confirmed positive for borax through the curcumin paper test. Two of those four samples showed the same flame color as standard corresponding to the presence of borax as a preservative in skewered meatballs tested. These results indicate that the curcumin paper test and flame color test were compatible in identifying borax in skewered meatball samples qualitatively.